Ferromanganese crusts from the seamounts north of the Madeira Island : composition, origin and paleoceanographic conditions - Muinos, Susana (2015)
This work studies ferromanganese deposits from the northeast Atlantic Ocean in an integrated way, considering them both as paleoceanographic archives and as potentially economic resources.